Insomnia Symptoms, Mental Health Diagnosis, Mental Health Care Utilization, and Perceived Barriers in U.S. Males and Females - Sawadogo, Wendemi; Njoku, Anuli; Jegede, Joy (Journal of Clinical Medicine, 2025)
Objective: We aim to determine the association between insomnia symptoms and mental health in females and males and compare mental health care utilization and perceived barriers between females and males with insomnia symptoms. Methods: This is a cross-sectional study using the National Health Interview Survey. Insomnia symptoms included self-reported “trouble falling asleep”, ‘trouble staying asleep”, and “waking up feeling not well rested”. Mental health included self-reported anxiety and depression. Multivariable logistic regression was used to assess the association between insomnia symptoms and mental health in females and males. Results: A total of 26,691 adults were included. The mean age was 48.2 years; 51.4% were females, and 48.6% were males. Insomnia symptoms were associated with anxiety and depression for both females and males. These associations were stronger in younger adults (<50 years) than older adults (≥50 years). Females with insomnia symptoms were more likely to receive mental health care (OR = 1.7; 95% CI = 1.53, 1.87) but also to delay mental health care because of its cost (OR = 1.96; 95% CI: 1.67, 2.30) or needed mental health care but did not get it because of the cost (OR = 2.14; 95% CI: 1.82, 2.50) than their males counterpart. Conclusions: Insomnia symptoms were associated with mental health in females and males, being stronger in younger adults than older adults, with gender differences in mental health care utilization and financial barriers to mental health care. Holistic approaches involving prevention and better access to mental health care are warranted.
Keywords: Anxiety; Cross-sectional study; Depression (economics); Feeling; Health care; Insomnia; Internal medicine; Logistic regression; Medicine; Mental health; Psychiatry; Psychology; dept.pch; dept.swk; peer-reviewed

Racial and ethnic disparities in cancer occurrence and outcomes in rural United States: a scoping review - Njoku, Anuli; Sawadogo, Wendemi; Frimpong, Princess (Cancer Control, 2024)
BackgroundCancer is the second-leading cause of death in the United States. Most studies have reported rural versus urban and Black versus White cancer disparities. However, few studies have investigated racial disparities in rural areas.ObjectiveWe conducted a literature review to explore the current state of knowledge on racial and ethnic disparities in cancer attitudes, knowledge, occurrence, and outcomes in rural United States.MethodsA systematic search of PubMed and Embase was performed. Peer-reviewed articles published in English from 2004-2023 were included. Three authors independently reviewed the articles and reached a consensus.ResultsAfter reviewing 993 articles, a total of 30 articles met the inclusion criteria and were included in the present review. Studies revealed that underrepresented racial and ethnic groups in rural areas were more likely to have low cancer-related knowledge, low screening, high incidence, less access to treatment, and high mortality compared to their White counterparts.ConclusionUnderrepresented racial and ethnic groups in rural areas experienced a high burden of cancer. Improving social determinants of health may help reduce cancer disparities and promote health.
Keywords: dept.pch; peer-reviewed

WIC Participation During Pregnancy and Low and Very Low Birth Weight by Race and Ethnicity - Sawadogo, Wendemi; McGuire, Neil; Evans, Marian; Tangbe, Praise (Journal of Nutrition Education and Behavior, 2025)
Keywords: Anthropology; Biology; Ethnic group; Gender studies; Low birth weight; Medicine; Obstetrics; Pregnancy; Race (biology); Sociology; WIC; dept.pch; low birth weight; peer-reviewed; pregnancy; race and ethnicity; very low birth weight

A Scoping Review of Skin Whitening Products: Users’ Knowledge and Motivations, Marketing Strategies, and Adverse Health Effects - Njoku, Anuli; Sawadogo, Wendemi; Pierce, Taryn; Albert, Kaleigh; Plummer, Fabian (International Platform of Registered Systematic Review and Meta-analysis Protocols, 2025)
Keywords: Adverse effect; Business; Marketing; Medicine; Pharmacology; dept.pch

Insomnia symptoms and the risk of all-cause mortality among stroke survivors - Sawadogo, Wendemi; Adera, Tilahun; Alattar, Maha; Perera, Robert; Burch, James (BMC Public Health, 2024)
Insomnia is more frequently reported in stroke survivors but its independent role in mortality in stroke survivors is unknown. The purpose of this study was to investigate the association of insomnia symptoms with all-cause mortality among stroke survivors.
Keywords: Age difference; All-cause mortality; Insomnia symptoms; Sex difference; Stroke survivors; dept.phc; peer-reviewed

Maternal prepregnancy body mass index and risk of preterm birth: the role of weight gain during pregnancy, race, and ethnicity - Sawadogo, Wendemi; Tsegaye, Medhin; Gizaw, Andinet; Newland, Hunter; Adera, Tilahun (American Journal of Perinatology, 2024)
Objective Preterm birth (PTB) is one of the leading causes of infant and neonatal mortality. Prepregnancy body mass index (BMI; kg/m2) has been linked to PTB but the evidence of this association by weight gain during pregnancy, race, and ethnicity is limited. This study aimed to assess the association between maternal prepregnancy BMI and PTB stratified by weight gain during pregnancy, race, and ethnicity. Study Design The U.S. natality data from 2017 to 2021 were used. In this analysis, we included mothers who had a live singleton birth and available data for prepregnancy BMI, gestational age at birth, weight gain during pregnancy, race, and ethnicity. Logistic regression models were used to assess the association between prepregnancy BMI categories and PTB stratified by weight gain during pregnancy, race, and ethnicity. Results A total of 17,311,509 singleton live births were included of which 1,393,889 (8.05 %) were PTBs. After adjusting for confounders, compared with normal prepregnancy BMI mothers (18.5–24.9), those with underweight BMI (<18.5) were at increased odds of PTB regardless of weight gain during pregnancy, race, and ethnicity. However, for mothers with a prepregnancy BMI above the normal weight (≥25), the association between prepregnancy BMI and PTB differs by weight gain during pregnancy, race, and ethnicity. Asian mothers with obesity II (35.0–39.9) had 93% (odds ratio [OR] = 1.93, 95% confidence interval [CI]: 1.62–2.30) increased odds of PTB for weight gain during pregnancy of 31 to 40 pounds. Their White, Hispanic, and Black counterparts experienced lower odds of PTB for similar weight gain during pregnancy (White: OR = 1.56, 95% CI: 1.51–1.60; Hispanic: OR = 1.48, 95% CI: 1.41, 1.54; and Black: OR = 1.22, 95% CI: 1.17–1.27). Conclusion Mothers with underweight BMI were at increased risk of PTB regardless of weight gain during pregnancy, race, and ethnicity. However, the association between high prepregnancy BMI and PTB varied by weight gain during pregnancy, race, and ethnicity. Key Points
Keywords: body mass index; dept.pch; ethnicity; obesity; peer-reviewed; pregnancy; preterm birth; race; weight gain during pregnancy

Association Between Social Determinants of Health and Borderline Personality Disorder: A Systematic Review - Guerrera, Patrick; Sawadogo, Wendemi; Baviskar, Snehal; Pham, Julie; Patel, Nirali; Cyrus, John (Personality and Mental Health, 2025)
Keywords: Association (psychology); Borderline personality disorder; Context (archaeology); Interpersonal relationship; Mental health; Personality; PsycINFO; Social determinants of health; borderline personality disorder; dept.pch; education; income; social determinants of health; social support; socioeconomic status

Sleep Duration, Disturbances, and Health-Related Quality of Life in Stroke Survivors - Sawadogo, Wendemi; Adera, Tilahun; Burch, James; Alattar, Maha; Perera, Robert; Howard, Virginia (Archives of Physical Medicine and Rehabilitation, 2025)
Keywords: Insomnia; Odds; Odds ratio; Quality of life; Quality of life (healthcare); Rehabilitation; Sleep (system call); Sleep disturbances; Sleep duration; Stroke (engine); Stroke survivors; dept.pch

Exposure to Endocrine-Disrupting Chemicals and Early Onset of Menarche: A Systematic Review - Njoku, Anuli; Al-Hassan, Mousa; Tohura, Sharaban; Albert, Kaleigh; Pierce, Taryn; Sawadogo, Wendemi (Pollutants, 2025)
There has been a decline in the age at which girls experience menarche worldwide. Research suggests that exposure to endocrine-disrupting chemicals is linked to negative health consequences, including early onset of menarche. This systematic review examined the association between exposure to endocrine-disrupting chemicals (EDCs) and the early onset of menarche. Comprehensive searches of the PubMed, Embase, Web of Science, and Scopus databases were conducted to find relevant studies published from inception to November 2024. Exposure to certain EDCs, such as particulate matter and phthalates, showed significant associations with earlier menarche onset, while exposure to other EDCs (e.g., pyrethroids) was linked to delayed menarche timing. Overall, there were mixed findings in the relationships between various EDC exposures and menarche onset. Few studies investigated how exposure to EDCs and early menarche differed by race and ethnicity. This underscores the need for more studies that examine the relationship between early menarche onset and exposure to endocrine-disrupting substances. Education and policy approaches are also warranted to address this issue.
Keywords: Age of onset; Epidemiology; MEDLINE; Menarche; Risk assessment; Scopus; dept.pch; endocrine-disrupting chemicals; environmental health; menarche; puberty; reproductive health

Sleep duration and all-cause mortality among stroke survivors - Sawadogo, Wendemi; Adera, Tilahun; Burch, James B.; Alattar, Maha; Perera, Robert; Howard, Virginia J. (Journal of Stroke and Cerebrovascular Diseases, 2024)
Background Post stroke sleep duration could increase the risk of death. This study tested the hypothesis that inadequate sleep duration is associated with increased mortality among stroke survivors. Methods The REasons for Geographic And Racial Differences in Stroke (REGARDS), a national population-based longitudinal study, was the data source. Sleep duration was ascertained between 2013 and 2016 among stroke survivors who were subsequently followed up until death or censored on December 31, 2022. Sleep duration was estimated as the difference between wake-up time and bedtime to which was subtracted the time spent in bed without sleep. Cox proportional hazards regression models were employed to investigate the association between sleep duration and all-cause mortality adjusting for demographic factors, socioeconomic factors, behavioral factors, and co-morbidities. Results A total of 468 non-Hispanic Black and White stroke survivors were included in this analysis. The mean age was 76.3 years, 52.6% were females and 56.0% were non-Hispanic White individuals. The distribution of short (≤6 h), adequate (7.0–8.9 h), and long sleep (≥9 h) was 30.3%, 44.7%, and 25%, respectively. Over a mean follow-up of 5.0 years, 190 (40.6%) deaths occurred. Compared to stroke survivors with adequate sleep (7.0–8.9 h), stroke survivors with long sleep (≥9 h) were at increased risk of all-cause mortality (HR=1.46, 95% CI=1.01, 2.12). However, short sleep (≤6 h) was not significantly associated with an increased risk of all-cause mortality (HR=1.31, 95% CI=0.90, 1.91). Subgroup analyses indicated higher risk in the age <75 years, females, non-Hispanic Black individuals, and those living in the Stroke Belt region, but those differences were not statistically significant. Conclusion In this study of stroke survivors, 9 hours or more of sleep per day was associated with an increased risk of all-cause mortality. This finding suggests that excessive sleep duration may be a warning sign of poor life expectancy in stroke survivors.
Keywords: All-cause mortality; Cohort study; Sleep duration; Stroke survivors; dept.pch; peer-reviewed

The Relationship Between Sleep Disorders and Stroke - Sawadogo, Wendemi; Adera, Tilahun (Handbook of the Behavior and Psychology of Disease, 2025)
Stroke is a leading cause of death and disability worldwide. It is a serious disease caused by a disruption of blood flow in the brain resulting from either blockage of blood flow to the brain (ischemic stroke) or sudden bleeding in the brain (hemorrhagic stroke). Stroke survivors experience more sleep disorders than the general population. Sleep disorders could also increase the risk of stroke even in individuals who have no history of stroke. Obstructive sleep apnea and insomnia are the most common sleep disorders associated with increased risk of stroke. Long sleep duration (≥9 h/day) and circadian rhythm changes have also been linked to an increased risk of stroke. This chapter summarizes the current evidence on the relationship between sleep disorders and stroke. © 2025 Springer Nature Switzerland AG.
Keywords: Central sleep apnea; Circadian rhythm disruption; Hypersomnia; Insomnia; Obstructive sleep apnea; Parasomnia; Sleep disorders; Sleep disturbances; Sleep movement disorders; Stroke; dept.pch

Impact of an emergency department take-home naloxone program on subsequent overdose and death - Wills, Brandon; Keyser‐Marcus, Lori; Sawadogo, Wendemi; Gizaw, Andinet; Melmer, Monica; Nguyen, Tammy; Nguyen, Natalie; Davis, Theresa; Ringwood, Katy; Moeller, F. (Heliyon, 2025)
Abstract Background Patients presenting to the emergency department (ED) following nonfatal opioid overdose represent a high-risk population with 5 % of patients dying within a year of the index visit. Objective To evaluate subsequent overdose and death before and after the implementation of an ED discharge naloxone program. Methods This was a retrospective cohort study of ED patients who presented at the Virginia Commonwealth University Health ED with an Opioid Use Disorder (OUD) chief complaint before and after a discharge naloxone program. The pre-naloxone cohort was consecutive ED OUD patients from August 15, 2021, to August 14, 2022, and the post-naloxone cohort from August 15, 2022, to August 14, 2023. The outcomes were subsequent overdose, ED visit to same hospital (VCU), and death within six months of the index visit. Results In total, 1,053 patients were included, of which 529 were in the pre-naloxone cohort and 524 patients in the post-naloxone cohort. The mean age was 44.2 years (SD = 14.0) and 69 % were males. There was a reduction in overdose requiring ED visiting (subsequent ED overdose) and death (4.6 % vs 9.2 % p = 0.03 and 2.0 % vs 5.6 % p = 0.02 respectively) in the post-naloxone cohort compared to the pre-naloxone cohort. After adjusting for sociodemographic and clinical factors, there was a 48 % reduction in the risk of subsequent ED overdose (RR = 0.52, 95 % CI: 0.27, 1.02) and a 63 % reduction in the risk of death (RR = 0.37, 95 % CI: 0.14, 0.95). Conclusion Implementing an ED take-home naloxone program was associated with a reduction in subsequent overdose and death at six months.
Keywords: (+)-Naloxone; Drug overdose; Emergency department; Emergency medicine; Internal medicine; Medical emergency; Medicine; Naloxone; Opioid; Opioid antagonist; Opioid overdose; Poison control; Psychiatry; dept.pch; peer-reviewed